Happiness, Pain Intensity, Pain Interference, and Distress in Individuals with Physical Disabilities. (December 2015) - Müller, Rachel; Terrill, Alexandra L.; Jensen, Mark P.; Molton, Ivan R.; Ravesloot, Craig; Ipsen, Catherine
ABSTRACT: Objectives: The aim of this study was to examine how the construct of happiness is related to pain intensity, pain interference, and distress in individuals with physical disabilities. Design: This study involves cross-sectional analyses of 471 individuals with a variety of health conditions reporting at least mild pain. Results: The first hypothesis that happiness mediates the relationship between pain intensity and two outcomes, pain interference and distress, was not supported. The second hypothesis was supported by a good fitting model (χ 2 10 = 12.83, P = 0.23, root-mean-square error of approximation = 0.025) and indicated that pain intensity significantly mediated the effect of happiness on pain interference (indirect effect: β = −0.13, P < 0.001) and on distress (indirect effect: β = 0.10, P = 0.01). Happiness showed a significant direct effect on pain intensity ( β = −0.20, P < 0.001). A third model exploring the happiness components meaning, pleasure, and engagement fitted well (χ 2 4 = 9.65, P = 0.05, root-mean-square error of approximation = 0.055). Pain intensity acted as a significant mediator but only mediated the effect of meaning on pain interference (indirect effect: β = −0.07, P = 0.05) and on distress (indirect effect via pain interference: β = −0.04, P = 0.05). Only meaning ( β = −0.10, P = 0.05), but neither pleasure nor engagement, had a significant direct effect on pain intensity. Conclusions: Participants who reported greater happiness reported lower pain interference and distress through happiness' effects on pain intensity. Experiencing meaning and purpose in life seems to be most closely (and negatively) associated with pain intensity, pain interference, and distress. Findings from this study can lay the groundwork for intervention studies to better understand how to more effectively decrease pain intensity, pain interference, and distress.